Transposition rates of movable genetic elements in Drosophila melanogaster. - Harada, K (1990)
A considerable proportion of visible mutations is reported to be caused by the insertion of mobile genetic elements in Drosophila and other organisms. We estimated transposition rates of some Drosophila mobile elements by using the lines AW and JH in which spontaneous mutations have been accumulated independently for about 400 generations. Occupied sites of the mobile elements were detected by in situ hybridization on the salivary gland chromosomes sampled from 40 AW and 30 JH lines. The rates of insertion and excision of the copia and two copia-like elements, 412 and 17.6, are very low: Insertions occurred at up to 10(-3) per second chromosome per generation (17.6) and excision occurred at about 10(-5) per site per generation (copia and 412). Insertions of the I and hobo elements occurred much more frequently. These estimates are not only important for assessing the actual rate of various types of mutations but also for developing an evolutionary theory of mobile elements themselves.